Pemanfaatan Hukum Internasional dalam Penyelesaian Sengketa Laut China Selatan: Analisis dengan Pendekatan Doktrinal - Soeparan, Poppy Fitrijanti; Kossay, Methodius (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The South China Sea is a strategic region of global significance, both economically and geopolitically. It serves as a major global trade route, with over 30% of global trade passing through it annually. Additionally, the South China Sea is rich in natural resources, including oil, gas, and abundant marine products. However, overlapping territorial claims among countries such as China, the Philippines, Vietnam, Malaysia, Brunei, and Indonesia have triggered prolonged geopolitical tensions. This study aims to analyze the role of international law, particularly UNCLOS 1982, as the primary framework for resolving these disputes. Using a doctrinal approach, the study examines primary legal documents, such as UNCLOS 1982, the 2016 Arbitration Award, and ASEAN agreements. Data shows an average of 15 annual conflicts in the South China Sea over the past decade, with a significant increase from 5 cases in 2014 to 25 cases in 2023. While UNCLOS 1982 provides a clear legal framework, non-compliance with arbitration rulings, such as China's refusal to adhere to the 2016 ruling, highlights weaknesses in enforcement mechanisms and sanctions. This study emphasizes that multilateral approaches based on international law, supported by regional mechanisms like ASEAN, have yet to achieve full effectiveness. The findings offer strategic recommendations, including reforming international sanction mechanisms and strengthening ASEAN frameworks to support conflict resolution and ensure sustainable stability in the region